The predictive role of intolerance of uncertainty and trait of worry in breast cancer patients: A prospective, observational, single-center clinical study - Shams, Malihe; Pardini, Susanna; Del Bianco, Paola; Calabrese, Caterina; De Salvo, Gian Luca; Novara, Caterina (Frontiers in Psychology, 2023)
Background: Breast cancer diagnosis and treatment compromise well-being in a pervasive way, and negative consequences may remain after recovery. The psychological side of breast cancer has been extensively investigated; however, the role of intrusive thoughts and intolerance of uncertainty have been studied less systematically. Objectives: The present study aimed to prospectively evaluate worry content, depression, anxiety, and post-traumatic stress symptoms and to define the role of the trait of worry and intolerance of uncertainty (IU) related to breast cancer. Methods: Patients with their first breast cancer diagnosis were enrolled in a single-center, prospective observational trial. The trait of worry and IU were assessed using the Penn State Worry Questionnaire (PSWQ) and the Intolerance of Uncertainty Scale-Revised (IUS-R). The psychological aspects were evaluated using the Worry Domains Questionnaire (WDQ), the Beck Anxiety (BAI), Beck Depression Inventory-II (BDI-II), and the Impact of Event Scale-Revised (IES-R). Questionnaires were administered in a randomized sequence at diagnosis (T0), three months post-diagnosis (T1), and 12 months post-diagnosis (T2). Results: 150 eligible patients were enrolled in the study and provided the T0 assessment. Further compliance rates were 57% at T1 and 64% at T2. All patients showed a significant and continuous increase in the IES-R scale (p<0.0001) from diagnosis to the end of the study, while no significant changes were observed for the WDQ, BAI, and BDI-II scales. The clinical PSWQ levels and/or high levels of the IUS-R score were the only variables that aided the distinction between patients who maintain high levels of depression, anxiety, and post-traumatic disorders and those who did not. Conclusion: An early assessment of the components of the trait of worry and intolerance of uncertainty could be critical in identifying patients with a higher psychopathological risk. Furthermore, if future studies confirm the present findings, support and monitoring throughout the prognosis may present crucial benefits, and possibly affect the course of treatment. Keywords: Breast cancer, intolerance of uncertainty, trait of worry, longitudinal study, psychological assessment